Pertanggungjawaban Pidana Terhadap Pelaku Pengguntingan Bendera Negara Republik Indonesia - Renny Obertina Julita Iwamony; John Dirk Pasalbessy; Margie Gladies Sopacua (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: The crime of insulting the Red and White flag in Karawang, West Java and Malasya, the flag with a hammer picture at Hassanudin University and the flag brushed with a Water Closet (WC) brush violates the provisions of Article 66 of the Law of the Republic of Indonesia Number 24 of 2009 in conjunction with Article 24 Letter a Law Number 24 Year 2009Purposes of the Research: Analyzing and explaining whether the perpetrators of insulting the flag can be held criminally responsible and forms of criminal responsibility for the act of insulting the red and white flag.Methods of the Research: It is normative juridical, using a legal, conceptual and case approach with primary and secondary legal materials and will be analyzed qualitatively.Results of the Research: Criminal liability from the first to the third case fulfills the five elements of responsibility, namely, there are perpetrators of criminal acts; there is an action; There is a mistake; capable of being responsible and against the law. Furthermore, the fourth case cannot be held accountable because the subject who committed the crime has a mental disorder that is not in accordance with the elements of criminal responsibility in Article 44 of the Criminal Code. The form of criminal liability in the first to third cases is individual, meaning that individual criminal responsibility is the form embedded in the case.